Distance learning via MOOCs: Improving esl learners’ writing skills - Shabani Jasni, Nurakhma; Hashim, Harwati; Md Yunus, Melor; Abd Rahman, Siti Fatimah (IOP Publishing, 2019)
Students nowadays are exposed to technology and they are always interested in learning new things. By incorporating technology as a means of learning, the students would be able to develop interest in learning language and improving their ICT skills. Crossing the line of time and distance and applying the saying that learning could be done anywhere and every time, applying the theory of distance learning, this paper reviews the effectiveness using MOOCs to improve students’ writing skills. Prior research regarding the use of MOOCs and technology, especially in language education and writing skills, is reviewed. Emphasizing on MOOCs as the platform of improving students’ writing skills, this paper explains how MOOCs helps in improving the process of teaching and learning and the importance of self-directed learning.